Perceptions and Anticipations towards AI-Enhanced Risk Management in Agile Project Management: A Comparative Survey-Based Analysis of PMBOK and PRINCE2 Methodologies - Deb, Siddhartha (Digital Repository of Theses, 2023)
This research probes project management practitioners' perceptions and anticipations regarding integrating AI tools in risk management within Agile contexts, mainly focusing on PMBOK and PRINCE2 frameworks. The impetus for this inquiry emerges not only from the ongoing transformative shifts in the realm of project management due to AI advancements but also from notable literature gaps and corporate business requirements. Specifically, these gaps include a comprehensive comparative analysis of PMBOK and PRINCE2 in Agile risk management settings and a discernible need for in-depth studies exploring the tangible benefits and challenges of AI's role in fortifying risk management within these predominant frameworks. Additionally, there needs to be more empirical research combining PMBOK, PRINCE2, Agile strategies, risk management paradigms, and the cutting-edge frontiers of AI. This investigation responds to these pressing demands, aiming to shed light on AI's real-world applicability and implications in contemporary project management practices. A mixed-method approach was employed to understand these facets, encompassing qualitative and quantitative methods deeply—a structured survey furnished insights into broad trends surrounding AI's anticipated challenges and benefits. A qualitative probe, rooted in a comprehensive literature survey on PMBOK and PRINCE2, was realized through practitioner interviews. These engagements elucidated real-world experiences and challenges, showcasing determinants of successful AI integration in Agile using these frameworks. Triangulated findings spotlight PMBOK and PRINCE2's allure for AI-augmented risk management in Agile scenarios. Practitioners expressed optimism about AI's capability to refine the risk management process. Nonetheless, specific barriers were underscored, which include the 'black box' issue, data privacy, integration challenges, and the need for AI-focused training, implying change management demands and cost considerations. The study reveals an apparent enthusiasm among practitioners for AI's role in enhancing risk management, balanced by acknowledging the inherent challenges. While PMBOK and PRINCE2 are viewed as potent vehicles for AI integration, practitioners emphasize the importance of methodological agility, continuous upskilling, and fostering an innovative ethos. The preparedness and adaptability in addressing AI-specific challenges are paramount. This research adds to the current discussions on theory, provides a plan for further exploration, and gives practical advice for businesses and professionals on the verge of integrating Agile methodologies with AI.